A humanized monoclonal antibody that inhibits platelet‐surface ERp72 reveals a role for ERp72 in thrombosis. (15th January 2018) - Holbrook, L.‐M.; Sandhar, G. K.; Sasikumar, P.; Schenk, M. P.; Stainer, A. R.; Sahli, K. A.; Flora, G. D.; Bicknell, A. B.; Gibbins, J. M.
Abstract : Essentials ERp72 is a thiol isomerase enzyme. ERp72 levels increase at the platelet surface during platelet activation. We generated a humanized monoclonal antibody which blocks ERp72 enzyme activity (anti‐ERp72). Anti‐ERp72 inhibits platelet functional responses and thrombosis. Summary: Background: Within the endoplasmic reticulum, thiol isomerase enzymes modulate the formation and rearrangement of disulfide bonds in newly folded proteins entering the secretory pathway to ensure correct protein folding. In addition to their intracellular importance, thiol isomerases have been recently identified to be present on the surface of a number of cell types where they are important for cell function. Several thiol isomerases are known to be present on the resting platelet surface, including PDI, ERp5 and ERp57, and levels are increased following platelet activation. Inhibition of the catalytic activity of these enzymes results in diminished platelet function and thrombosis. Aim: We previously determined that ERp72 is present at the resting platelet surface and levels increase upon platelet activation; however, its functional role on the cell surface was unclear. We aimed to investigate the role of ERp72 in platelet function and its role in thrombosis. Methods: Using HuCAL technology, fully humanized Fc‐null anti‐ERp72 antibodies were generated. Eleven antibodies were screened for their ability to inhibit ERp72 activity and the most potent inhibitory antibody (anti‐ERp72) selected for further testing in platelet functional assays. Results and conclusions: Anti‐ERp72 inhibited platelet aggregation, granule secretion, calcium mobilisation and integrin activation, revealing an important role for extracellular ERp72 in the regulation of platelet activation. Consistent with this, infusion of anti‐ERp72 into mice protected against thrombosis.